Towards a Cradle‐to‐Cradle Polyolefin Lifecycle - Thevenon, Arnaud; Vollmer, Ina (Angewandte Chemie International Edition, 2023)
Achieving efficient chemical depolymerization of waste polyolefins to monomers remains an unsolved challenge, while it could be an effective means to avoid further waste accumulation in the environment and generate economic benefits. In a recent publication by Conk et al., polyethylene (PE) is converted to propylene, the second most used monomer in the polymer industry. The conversion is achieved via a tandem catalysis approach in which partially unsaturated PE chains react with ethylene to generate propylene with yields as high as 87 %. The study is a first proof of concept showcasing a selective chemical depolymerization of PE to a monomer. Future research is expected to focus on the catalyst optimization, process design, and compatibility with contaminated and multi‐polymer waste streams. Selective depolymerization of polyethylene to propylene was achieved by two independent studies using a tandem catalysis approach. By combining a dehydrogenation, an isomerization and an ethenolysis catalyst under an ethylene atmosphere, propylene was the favoured product which could be further used as precursor for polypropylene production.